2020
DOI: 10.1038/s41537-019-0092-x
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine-induced transcriptional changes in the zebrafish brain

Abstract: Clozapine is an atypical antipsychotic medication that is used to treat schizophrenia patients who are resistant to other antipsychotic drugs. The molecular mechanisms mediating the effects of clozapine are not well understood and its use is often associated with severe side-effects. In this study, we exposed groups of wild-type zebrafish to two doses of clozapine ('low' (20 µg/L) and 'high' (70 µg/L)) over a 72-h period, observing dose-dependent effects on behaviour. Using RNA sequencing (RNA-seq) we identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…At a broader level however, it is worth noting that associations between antipsychotics and side-effects, and enrichment of relevant biological pathways were observed across all compounds, despite their differing MoAs. Further comparison in different biological models, including those where ageing and frailty can be incorporated, and epidemiological studies is now warranted [33]. The overall trend towards downregulation of genes in this experiment is also worth comment.…”
Section: Discussionmentioning
confidence: 85%
“…At a broader level however, it is worth noting that associations between antipsychotics and side-effects, and enrichment of relevant biological pathways were observed across all compounds, despite their differing MoAs. Further comparison in different biological models, including those where ageing and frailty can be incorporated, and epidemiological studies is now warranted [33]. The overall trend towards downregulation of genes in this experiment is also worth comment.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, aberrant epigenetic regulation of TGFB2 and alteration in TGFβ signaling might contribute to loss or reversal of brain laterality in SCZ cases. A previous study revealed that clozapine exposure is correlated with down-regulation of ANGPTl4 ( 89 ). Clozapine, an uncommon antipsychotic treatment, is used for SCZ patients with other antipsychotic drug resistance ( 90 ).…”
Section: Discussionmentioning
confidence: 97%
“…We therefore investigated the expression of proteins involved in mitochondrial function. The expression of PKMb is closely associated with the function of ETC (Prado‐Lima & Val, 2016), and CKma is known to regulate mitochondrial morphology and function including mitochondrial permeability transition pore (MPTP) and ΔΨ in zebrafish (Ding et al, 2017; Rickmann et al, 2007; Viana et al, 2020). HSP90 and HSC70 regulate mitochondrial protein turnover (Margineantu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%